2010
DOI: 10.2319/011509-535.1
|View full text |Cite
|
Sign up to set email alerts
|

Root Contact during Drilling for Microimplant Placement

Abstract: Objective: To determine the surgery site dependency of root contact during drilling for orthodontic microimplant placement and to analyze the influence of clinicians' expertise on the results. Materials and Methods: Dental arches with resin teeth were mounted on a dental phantom (P-5/3 TS, Frasaco, Germany). Drilling was conducted in six locations frequently selected for microimplant placement: between the central incisors, between the maxillary first molar and second premolar, and between the mandibular first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 10 publications
(22 reference statements)
3
24
0
1
Order By: Relevance
“…This inflammation may be more a result than a cause of failure since it cannot be controlled by improving oral hygiene (11). We agree with Cho et al (10) that, between the three right-handed operators observed in this study, the habitual posture developed with clinical experience could have a negative impact on success rates, depending on the surgery site, which may affect the view angle and instrument access, although these factor deserves further investigation.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This inflammation may be more a result than a cause of failure since it cannot be controlled by improving oral hygiene (11). We agree with Cho et al (10) that, between the three right-handed operators observed in this study, the habitual posture developed with clinical experience could have a negative impact on success rates, depending on the surgery site, which may affect the view angle and instrument access, although these factor deserves further investigation.…”
Section: Discussionsupporting
confidence: 72%
“…This side also exhibited greater failure rates in other studies, with (22) or without (1,4,15,16) statistically significant evidence to account for differences in the success rate. This result may be related to factors such as preferred side of mastication, access difficulties when placing the OMS or viewing the right or left side (7,10,22), different levels of oral hygiene among righties and lefties (23,24), and random statistical errors (5). Studies differ when trying to show that right-handed (24) or left-handed (25) patients keep better hygiene, or attempting to prove that manual dexterity is not linked to plaque control (23), but motivation is.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 What is more, Cho et al found that the higher the number of performed micro-implantations, the lower the risk of damaging an adjacent root. 44 A comparison of the stability of micro-implants inserted by a maxillofacial surgeon and an orthodontist showed no significant differences, indicating that orthodontists are fully capable of performing successful micro-implantations after they have gained the necessary experience.…”
Section: Operator's Experiencementioning
confidence: 99%
“…Although orthodontic anchor screws reduce the burden on patients and help in attaining treatment goals, many patients develop complications such as loosening and deciduation of anchor screws, infection, pain and swelling around the placement site, and contact with and injury to the proximal teeth roots [9][10][11][12] . Despite their advantages over extraoral anchorage methods, anchor screws can occasionally loosen during treatment and eventually fail to provide firm anchorage [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%